Germination capability of Amaranthus spp. in different salts, salts stress alleviation and hydrotime model analysis - Idris, Leni Marlina (2018)
Salinity continues to be one of the abiotic stresses which effect plant especially at the germination and early seedling growth. Extensive amount of lands in the world is affected by salinity and is increasing day by day due to secondary salinization. The continuous crop cultivation on same land, improper irrigation technique as well as overuse of fertilizers intensify the soil salinity problems in Malaysia. Despite most of the salinity studies were on sodium chloride as saline condition, it is hypothesized that other salts may affect the plant growth. However, study on the effect of other salts on seed germination and early seedling growth remains insufficient. The effects of sodium chloride (NaCl), potassium chloride (KCl), magnesium chloride (MgCl2) and magnesium sulphate (MgSO4) on the germination and early seedling growth of Amaranthus tricolor L. and the stress alleviation by inorganic compounds was carried out for this study. This study also aimed to evaluate the germination capability for four different species of Amaranthus namely Amaranthus hybridus L., Amaranthus viridis L., Amaranthus tricolor L. and Amaranthus giganticus L. using hydrotime model analysis. Ten sterilized seeds of A. tricolor were germinated in sterilized petri dishes containing 5 ml of deionized water (control), 50mM, 100mM, 150mM, 200mM, 250mM and 300mM of NaCl, KCl, MgCl2 and MgSO4 solution separately and placed in completely randomized design (CRD) in laboratory condition for seven days. Germination percentage, germination rate, mean germination time, relative injury rate, seed vigor and early seedling growth were measured. For the stress alleviation study, A. tricolor seeds which initially primed in 300mM NaCl for 72 hours to induce stress condition were germinated in solution of KCl (5, 10, 20, 30 and 50 mM), potassium nitrate (KNO3) (5, 10, 25, 50, 75 mM) and thiourea (TU) (1.0, 2.0, 3.5, 7.0 and 10.0 mM). Following this, the ideal concentration of KCl, KNO3 and TU was mixed together to study the effectiveness in alleviating salt stress on A. tricolor. One-way ANOVA at confidence level (p=0.05) was used to determine the significant difference between treatment followed by Tukey test for mean comparison. For the study on the germination capability using hydrotime model analysis, 25 seeds from each four different Amaranthus species were germinated in petri dishes at salinity condition with 0 (control), -0.3, -0.6, -0.9 and -1.2 MPa. Repeated probit regression analysis was used to evaluate the salinity sensitivity of each Amaranthus species. The data for this study was evaluated using SPSS windows version 24. Results showed that A. tricolor more tolerance to NaCl compared to KCl, MgCl2 and MgSO4 during germination. However, greater reduction was pronounced at early seedling growth of A. tricolor in NaCl compared to KCl. Salinity stress also decreased the seed vigor and increased relative injury rate. 50mM KCl was found to enhance the hypocotyl length of A. tricolor seedlings. However, MgCl2 and MgSO4 suggested to have inhibitory effects on the growth since abnormal seedlings were observed at all concentrations. Results found that 5mM and 10mM of KCl and 5mM, 10mM and 25mM of KNO3 showed positive effect on hypocotyl and early seedling growth of salt stressed A. tricolor while 1.0mM TU enhance the root growth. The combination of KNO3, KCl and TU solution at the optimum concentration increased the seedling growth compared to control with combination of KCl (5mM), KNO3 (10 mM) and TU (1.0 mM) give the highest seedling growth. Apart from that, in the hydrotime analysis of Amaranthus species, it showed that A. giganticus showed better tolerance towards salinity than A. hybridus, A. viridis and A. tricolor with more negative value of Ψb(50) compared to the other species. In conclusion, the presence of different salt components as well as increased in salt concentrations affects the germination and early seedling growth of Amaranthus sp. to a certain degree. Nevertheless, the availability of inorganic compounds helps to mitigate the salinity effects on Amaranthus sp. seedling growth. Variation in the degree of tolerance among different Amaranthus species to salt stress was observed with A. giganticus showed more tolerance.